Benefits and Harms of Low-Dose Rivaroxaban in Asian Patients With Atrial Fibrillation: A Systematic Review and Meta-analysis of Real-World Studies - Qian, Jun; Yan, Yi-Dan; Yang, Sheng-Yan; Zhang, Chi; Li, Wen-Yan; Gu, Zhi-Chun (Frontiers in Pharmacology, 2021)
Background: Low-dose prescription of rivaroxaban was common among patients with atrial fibrillation (AF) in Asia. However, the benefits and harms of rivaroxaban at a low dosage in Asian patients with AF remains unclear. Accordingly, we aimed to collect and summarize all available evidence to fill this important knowledge gap. Methods: In this systematic review and meta-analysis, we systematically searched databases of MEDLINE, EMBASE, and Cochrane Library for relevant studies from inception until February 23, 2021. Eligible retrospective nationwide or health insurance database studies or prospective registration studies that reported efficacy (stroke/systemic embolism), safety (major bleeding, intracranial hemorrhage, gastrointestinal bleeding), or other outcomes (myocardial infarction, death) of low-dose rivaroxaban in comparison with warfarin in AF patients were enrolled. Data extraction and study quality assessment were conducted by two authors independently. Low dosing of rivaroxaban (15/10 mg) was defined as the received dose lower than the recommended dose (20 mg) approved in most districts. Hazard ratio (HR) with 95% confidence intervals (95% CIs) was pooled using a random-effect model. Subgroup analyses were conducted according to different dose regimens. Sensitivity analyses were conducted by sequential elimination of each study from the pool. Since potential effect modifiers (patient demographics, differences of each study, and others) may lead to bias in primacy outcomes, we performed a meta-regression analysis to explore the influence of these factors on the primary efficacy and safety outcomes. Results: Totally, 12 studies involving 292,815 Asian patients with AF were included. All studies were detected as low to moderate risk bias. Low-dose rivaroxaban treatment in Asian AF patients was associated with a reduced risk of stroke/systemic embolism (HR: 0.76, 95% CI: 0.70–0.84, I2: 57.8%), major bleeding (HR: 0.72, 95% CI: 0.62–0.84, I2: 81.5%), and all-cause death (HR: 0.65, 95% CI: 0.58–0.73, I2: 81.7%) when compared with warfarin. Furthermore, consistent results were observed among different dose regimens (10/15/20 mg) in all the clinical outcomes (Pinteraction > 0.05 for each outcome). Meta-regression analysis failed to detect any potential confounding to impact the primacy outcomes. Conclusion: Insights from the present meta-analysis, we found that low-dose rivaroxaban, even at a dosage of 10 mg daily, was associated with a reduced risk of stroke/SE and bleeding than warfarin in Asian AF patients. However, owing to considerable heterogeneity among included studies, further prospective studies are required to confirm these findings.